Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi‐2D Perovskite Materials Using a High‐throughput Experimental Platform. (17th August 2022) - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens A.; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al.
Abstract: Reduced‐dimensional (2D or quasi‐2D) perovskites have recently attracted considerable interest due to their superior long‐term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi‐2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon‐chain length from ethylammonium (EA) to n ‐dodecylammonium (DA) through a high‐throughput platform. The results show that long‐chain cations in quasi‐2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal‐aging process. For short‐chain cations, increased‐dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D‐like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi‐2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X‐ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased‐dimensional phase redistribution. This study provides new insight into the thermal stability of quasi‐2D perovskites. Abstract : For shorter‐chain cations such as EA/PA, the steric hindrance effect is too weak to prevent the fusion of two adjacent pieces of crystals during the thermal‐aging process of Ruddlesden−Popper quasi‐2D perovskites. However, the steric‐hindrance effect provided by longer‐chain cations (e.g. AA/HA) is strong enough to create a barrier between two adjacent crystals that disables the increased‐dimensional fusion process.